Comparison of three testing methods of rock materials equations of state. Issue 4 (October 2021) - Liang, Wen; Chen, Rong; Nie, Zhengyue; Lu, Fangyun
Abstract: For rock materials, it is very important to use effective and reliable testing methods to obtain accurate Hugoniot parameters and further determine the equation of state (EOS) reflecting the intrinsic properties of materials. In this paper, taking marble as the experimental sample, three test methods of the Hugoniot EOS (i.e., symmetric, asymmetric, and reverse impacts) are proposed based on the first-class light gas gun experimental platform. The Displacement Interferometer System for Any Reflector is used to measure the speed history of the target plate and the arrival time of the shock wave. The electric probe is used to measure the speed of the flyer. Under the same launch conditions, at least three repeated experiments were conducted for each scheme. The experimental results showed that when the relative standard deviation (RSD) of the launch speed was controlled within 2%, the RSD of post-wave pressure and shock wave speed in the reverse impact method was the smallest, making it the best choice for the measurement of the Hugoniot EOS of rock materials. However, the symmetric impact can evaluate the impact flatness of the flying plate and the target plate by the time difference between the shock wave to reach different positions on the same plane of the target.